Examining the Social Validity of a Universal Intervention for Reducing Exclusionary Discipline through Stakeholder Voice. Issue 4 (2nd October 2022) - Furjanic, David; Mannan, Irin; Hamilton, Jillian C.; Nese, Joseph F. T.; Austin, Sean; Izzard, Sara; Nese, Rhonda N. T.
Abstract: Exclusionary disciplinary practices are utilized in schools despite limited benefits and associated negative student outcomes. Alternative strategies, such as Positive Behavioral Interventions and Supports, reduce exclusionary discipline practices, though research is limited in secondary settings. This study examines how student and school staff input was utilized throughout the iterative refinement of the Inclusive Skill-building Learning Approach (ISLA), an intervention to reduce exclusionary discipline practices in middle school through instructional and restorative practices. Intentional stakeholder involvement was hypothesized to impact acceptability and fidelity of implementation, critical for achieving intervention outcomes. Data across a two-year mixed methods approach indicate that engaging stakeholders throughout implementation enhanced fidelity. Quantitative findings demonstrate better understanding of stakeholder experiences. Implications for practice, limitations, and suggestions for future research are discussed.